Efficacy and safety of a proposed omalizumab biosimilar compared to the reference product in the management of uncontrolled moderate-to-severe allergic asthma: a multicenter, phase III, randomized, double-blind, equivalency clinical trial - Ghanei, Mostafa; Ghalebaghi, Babak; Sami, Ramin; Torabizadeh, Mehdi; Mirsadraee, Majid; Amra, Babak; Tavakol, Marzieh; Raji, Hanieh; Fallahpour, Morteza; Kiani, Arda; Abedini, Atefeh; Jabbari Azad, Farahzad; et al. (Frontiers in Immunology, 2024)
Allergic asthma has a considerable burden on the quality of life. A significant portion of moderate-to-severe allergic asthma patients need omalizumab, an anti-immunoglobulin-E monoclonal antibody, as an add-on therapy. In this phase III clinical trial P043 (Zerafil ® , CinnaGen, Iran) efficacy, safety, and immunogenicity were compared with Xolair ® (the originator omalizumab). The primary outcome was the rate of protocol-defined asthma exacerbations. Exacerbation rates, Asthma Control Test (ACT) results, spirometry measurements, immunogenicity, and safety were evaluated. Each subject received either medication with a dose ranging from 150 to 375 mg based on pre-treatment serum total IgE level (IU/mL) and body weight (kg) every two or four weeks for a duration of 28 weeks. Exacerbation rates were 0.150 (CI: 0.079-0.220) in the P043 group, and 0.190 (CI: 0.110-0.270) in the omalizumab group (per-protocol). The least squares mean differences of predicted Forced Expiratory Volume in the First second (FEV1) were -2.51% (CI: -7.17-2.15, P=0.29) and -3.87% (CI: -8.79-1.04, P=0.12), pre-and post-bronchodilator use.The mean ± SD of ACT scores at the screening and the last visit were 10. 62 ± 2.93 and 20.93 ± 4.26 in P043 and 11.09 ± 2.75 and 20.46 ± 5.11 in the omalizumab group. A total of 288 adverse events were reported for the 256 enrolled participants. Among all, "dyspnoea" and "headache" were the most reported ones. The overall incidence of adverse events (P=0.62) and serious adverse events (P=0.07) had no significant differences between the two groups. None of the samples were positive for anti-drug antibodies. P043 was equivalent to omalizumab in the management of asthma in reduction of exacerbations. There was no significant difference in other efficacy and safety parameters.